Bovine tunica albuginea conserved in honey as xenograft for cystoplasty in rats - Rodrigues,Aline Ferreira (2021)
ABSTRACT: Urinary bladder damages leading to few viable bladder tissue available might demand a challenging reconstructive surgery. In this context, biomaterials are valid alternatives for bladder reconstruction. This study evaluated the bovine tunica albuginea fragment as graft material for cystoplasty in rats and honey-preserved implant viability.Thirty Wistar rats were assigned to two groups: (1) a test group (T) with a circular 1.0-cm-diameterbovine tunica albuginea graft application in the apex region by a continuous absorbable (Polyglactin 910 5-0) suture with stitching of all bladder layers and (2) a simulation group (S) in which animals underwent only partial cystectomy. In addition, each of these groups was further divided into three subgroups according to euthanasia period on post-surgery day 7, 15 and 30.Two animals had self-limiting hematuria at postsurgical period. At necropsy, frequent crystals and adhesion to the peritoneum were observed. At the histopathological evaluation, animals from the T group euthanized by 15th postoperative day had layers disorganization and initial muscle development, while T group rats euthanized by 30th postoperative day showed complete urothelization. Urothelization pattern was similar in both groups. Moreover, the muscular layer formation was present in both groups, but more evident in S group animals. Nevertheless, inflammatory infiltrate and neovascularization were remarkably more intense in T group rats.It might be concluded that bovine tunica albuginea graft was successful in repairing rats’ bladder, being a good biomaterial option in reconstructive urinary vesicle surgery.